Islamic law and its application as penal code by the Islamic State of Iraq and Sham (ISIS) - Jacky Li Chun-Leung; Mohd Roslan Mohd Nor; Khairul Anuwar Mustaffa; Khalid bin Isa (Cogent Arts & Humanities)
The Islamic State of Iraq and Sham (and hereafter ISIS) is a globally renowned terrorist organisation. Although it was defeated in 2019, its threat continues to loom over the world. Even amidst the current global pandemic caused by COVID-19, there is no indication that ISIS will cease its acts of terror. As we enter a post-COVID era and strive for normalcy, it remains imperative for international societies to remain vigilant and stay informed about recent developments related to extremist groups like ISIS. When discussing ISIS, there is often a focus on the cruel acts committed by the group during times of war and their underlying ideological motivations for these brutalities. Images and videos depicting these horrific acts have circulated widely on social media platforms and continue to be extensively discussed by the public. The incorporation of Islamic law into the penal code during ISIS rule raises crucial questions about its integration. Understanding Islamic history and law in non-Muslim contexts is essential for addressing public misconceptions and negative stereotypes towards Muslims. It is important to distinguish between ordinary Muslims and extremist groups like ISIS, as their association with terrorism can perpetuate misunderstanding among non-Muslims. This article aims to clarify the application of Islamic law in the penal code implemented by ISIS. It assumes that readers may not have a comprehensive understanding of Islamic law and how it was utilised by ISIS in areas they controlled during times of conflict. This discussion will begin with an explanation of Islamic law, followed by an outline of the penal code enforced within these occupied zones, and finally delve into its sociological and cognitive implications for interpreting Islam.